More Evidence That the Healthcare Administrative Burden Is Real, Widespread and Has Serious Consequences; Comment on "Perceived Burden Due to Registrations for Quality Monitoring and Improvement in Hospitals: A Mixed Methods Study" - Albert J. Heuer (Kerman University of Medical Sciences, 2022)
Countries around the world have implemented programs to help monitor and enhance the quality of health services provided. Inherent in these programs and internal process improvement initiatives are an array of reporting requirements which often place a burden on clinicians and the organizations in which they function. Zegers and colleagues performed a mixed methods study on the perceived burden which these reporting requirements place on doctors, nurses, and other clinicians within three hospitals in the Netherlands. Like all studies, theirs has some minor limitations; most notably possible limits on generalizability from a limited sample. Nonetheless, their project makes a valuable contribution to the growing body of research which suggests that the burden has deleterious effects on clinicians and may well have an erosive impact on patient care.